Childhood obesity and reduction of hours of sleep: results from cross-sectional study - Marques, G (2018)
Childhood obesity is a prevalent condition in modern societies which can negatively impact people's health during life. Although there are several factors contributing to obesity, sleep duration has been pointed out as an important risk factor. This study, held in the district of Porto, Portugal, aimed to analyze the association between sleep duration and the nutritional status of school-aged children studying in Portugal. 1396 students from 35 and 3 public and private schools, respectively, were contacted, of which 829 participated in this study (9.2 +/- 0.38 years old; 50.3% male; 49.7% female). Age, sex, sleep duration, height, weight and body composition were registered trough a questionnaire. According to the obtained z-score for Body Mass Index (BMI), 22.9% of the children were overweight and 15.2% were obese. The mean of sleep duration was 9.7 +/- 1.08 hours and z-score for BMI was 0.78 +/- 1.21, demonstrating a statistically significant (p<0.01) weak negative correlation (r=-0.15) between sleep duration and z-score of BMI. Results were also stratified and analyzed by sex, and the same finding was observed. Therefore, the results suggest a negative association between sleep duration and overweight/obesity in these children. Although more studies are necessary, this finding highlights the need of a global approach which includes sleep assessment and counselling when promoting an appropriate nutritional status.